Veterans' perceptions of racial bias in VA mental healthcare and their impacts on patient engagement and patient-provider communication. Issue 9 (September 2020) - Eliacin, Johanne; Matthias, Marianne S.; Cunningham, Brooke; Burgess, Diana J.
Highlights: Perceived racial bias negatively impact veterans' healthcare engagement. Contextual factors influence perceptions of situational cues as identity-threatening. Increased diversity and person-centered care can help create identity-safe environments. Abstract: Objectives: Drawing from social identity threat theory, which posits that stigmatized groups are attuned to situational cues that signal racial bias, we examined how African-American veterans evaluate verbal and non-verbal cues in their mental health encounters. We also explored how their evaluations of perceived racial bias might influence their healthcare engagement behaviors and communication. Methods: We interviewed 85 African-American veterans who were receiving mental health services from the US Department of Veterans Affairs (VA), examining their views and experiences of race in healthcare. We analyzed the data using a constructivist grounded theory approach. Results: Participants identified several identity threatening cues that include lack of racial diversity representation in healthcare settings, and perceptions of providers' fears of Black patients. We describe how participants evaluated situational cues as identity threats, and how these cues affected their engagement behaviors and healthcare communication. Conclusion: Our findings revealed situational cues within clinical encounters that create for Black veterans, fear of being negatively judged based on stereotypes that have characterized African-Americans. Practice Implications: We discuss the implications of these findings and provide suggestions on how to create identity safe environments for minority patients that include delivery of person-centered care, and organizational structures that reduce providers' burnout.